JUAL BELI ONLINE DALAM PENINGKATAN KESEJAHTERAAN EKONOMI DALAM PANDANGAN ISLAM - Novita Sari; Siska Aryani (LA RIBA: Jurnal Perbankan Syariah, 2022)
This study was conducted todetermine online buying and selling to improve economic welfare in the Islamic view. In this study, it does not requirea place to research, but insteadu sesalot of literature research techniques. The data analysis technique used in this study is a qualitative data analysis technique. Theres ultsand discussion of this researcher concluded that accordingto Islam, Online Business is legally allowed as longas it does not contain elements that can damage it such as usury, fraud, fraud, cheating, and the like.